Movements of balance sheet items and liquidity nexus: Evidence from Serbian banking sector - Vesić, Tamara; Barjaktarović, Lidija (Industrija (Ekonomski institut, Beograd), 2020)
The subject of research in this paper are eight balance sheets (based on regular annual financial statements), with the aim of finding out the effect of fluctuations in balance sheet items on the movement of commonly used liquidity ratios on a sample of 10 leading Serbian banks in terms of balance sheet assets (Banca Intesa, Komercijalna, UniCredit, Societe Generale, Raiffeisen, AIK, Eurobanka, Erste Bank, Poštanska štednionica i Vojvodjanska), by applying Pearson's correlation coefficient for the period 2010-2017. The four most commonly used liquidity ratios were used as dependent variables, while individual balance sheet items (part of the liquidity formula) were used as independent variables. According to the conducted research, Serbian banking sector recorded positive performance i.e. was sufficiently liquid, from 2010 to 2017. Furthermore, very strong correlation was observed between an increase in cash and an increase in bank liquidity, while there was a moderate correlation between an increase in cash and average total liabilities. Moreover, the increase in loans and receivables from banks and other financial institutions had a significant impact on the increase of liquidity, as well as on the increase in provisions and equity. Finally, the increase in the value of owned property and deposits had a negative impact on liquidity ratios.